Projeto de Monitoramento e Telemetria de um Sistema BAJA utilizando LoRa e RTOS - Marmirolli, Guilherme (Universidade Federal de São Carlos, 2026)
BAJA SAE vehicles operate in adverse off-road environments, subject to vibrations, impacts, and large distances from reference stations, which makes real-time monitoring challenging with conventional wireless communication technologies that impose significant range and robustness limitations. In this context, this work presents the development and experimental validation of an embedded monitoring and telemetry system for BAJA SAE vehicles, based on LoRa communication and Real-Time Operating System (RTOS) task management. The proposed system consists of a custom printed circuit board designed for the acquisition of engine rotational speed, vehicle speed, continuously variable transmission (CVT) temperature, and triaxial acceleration data, using Hall-effect sensors (A3144), a Type-K thermocouple with MAX6675 interface, and an MPU6050 accelerometer. Data processing is performed by an ESP32 microcontroller running FreeRTOS, with task distribution across its dual-core architecture to ensure efficient real-time operation. Wireless data transmission is carried out through the E220-900T22D LoRa module operating at 915 MHz, while local data logging is implemented through an SD card interface. Experimental validation demonstrated temperature measurement error within the manufacturerspecified tolerance of approximately 2 °C, coherent sensor responses for rotational speed and vehicle speed with minor delay and damping effects, and proper accelerometer operation for gravitational acceleration detection. Field tests of the LoRa communication link confirmed compliance with the 500 m range requirement imposed by BAJA competition conditions. Sending 18 bytes, it achieved packet loss rates below 5% and -85 dBm received signal strength at this distance using omnidirectional 6 dBi antennas. The results validate the proposed architecture and demonstrate its technical feasibility for real-time telemetry applications in BAJA SAE competitions.
Monitoring and Telemetry Project for a BAJA System using LoRa and RTOS
Keywords: Embedded systems; Vehicle telemetry; LoRa; FreeRTOS; Baja SAE; Esp32; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO; 9. Indústria, Inovação e Infraestrutura